Management Practices of Cats Owned by Faculty, Staff, and Students at Two Midwest Veterinary Schools - Stella, Judith L.; Croney, Candace C. (TheScientificWorld, 2016)
Understanding cat owners’ housing, care, and management practices is important for promoting cat welfare. A survey study was conducted on the housing and management practices used for cats by students, faculty, and staff of The Ohio State University and Purdue University veterinary colleges. Subjects were 138 cat-owner dyads. Most cats (74%) were housed strictly indoors in keeping with common US veterinary recommendations. However, many did not implement best practices outlined for behavior and other welfare needs of indoor cats. The percentage of respondents placing resources where cats could be disrupted while using them was 31%, 53%, and 30% for resting areas, food/water dishes, and litter boxes, respectively. Many cats were not provided a litter box in a private area (35%), in multiple areas of the house (51%), or that was regularly washed (73%). Horizontal scratching opportunities were not provided to 38% of cats; 32% were not provided toys that mimic prey and 91% of cats were fed a diet consisting of >75% dry food. These findings suggest a need for more concerted efforts to educate owners about meeting their cats’ welfare needs so as to attenuate risks and improve cat physical and behavioral welfare outcomes.